The composition of Peruvian food - Collazos Ch., Carlos (1952)
The real appreciation of the nutritional status of a population requires full knowledge of all aspects of production and consumption. It is necessary to know the total available food, chemical composition and nutritive value. In addition, the dietary habits of the population and health disturbances that relate to nutrition. All these factors must be known before taking measures to adjust the production and distribution of food, in order to improve current eating habits.